1998
DOI: 10.1046/j.1365-3156.1998.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Filarial elephantiasis among Haitian women: social context and behavioural factors in treatment

Abstract: SummaryFew studies have addressed the social and behavioural aspects of lymphatic filariasis. The research reported here investigated the ethnographic context of filarial elephantiasis among women in Léogane, Haiti, and focused on explanatory models of the illness, the impact of the disease on women's lives, and the difficulties patients experienced in following a therapeutic regimen provided at a local hospital. Qualitative data were collected through focus group and individual interviews and direct observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 9 publications
4
69
1
Order By: Relevance
“…In Haiti, Coreil et al found that the risk of dysfunction and unhappiness was greater in marriages where the wife had physical manifestations of filariasis. 24 This is supported by data from coastal Ghana. 20 Gyapong et al 25 suggest that the physical and psychological burden borne by men has a negative impact on their marriage and employment prospects.…”
Section: Impact On Infected Individuals Current Knowledge About Lf's mentioning
confidence: 58%
See 3 more Smart Citations
“…In Haiti, Coreil et al found that the risk of dysfunction and unhappiness was greater in marriages where the wife had physical manifestations of filariasis. 24 This is supported by data from coastal Ghana. 20 Gyapong et al 25 suggest that the physical and psychological burden borne by men has a negative impact on their marriage and employment prospects.…”
Section: Impact On Infected Individuals Current Knowledge About Lf's mentioning
confidence: 58%
“…27 As the disease progresses, the individual's capacity to labour, both productively and reproductively, is increasingly hampered. Coreil et al 24 note that in the Haitian context, while impairment of mobility impacts upon the ability to garden or sell produce in the market, acute attacks are equally detrimental to individuals' ability to support themselves and their family. This finding is echoed by the work of Gyapong et al 25 and Suma et al 28 As the disease progresses, the affected individual becomes too severely disabled to contribute to household labour and further burdens the household economy.…”
Section: Impact Upon Lifestyle and Economic Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] The physical impairments faced by victims are compounded by the social and psychological implications of overt disease. 7,8 The cost of acute filariasis is estimated at more than four million Disability-adjusted life years (DALYs) worldwide, in addition to the economic burden of lost productivity and medical costs. [9][10][11][12][13] With the advent of simple and sensitive diagnostic techniques (ICT card tests) and new therapeutic strategies (drug combinations) as well as strategies to control morbidity, widespread interest has developed for the elimination of this disease.…”
Section: Introductionmentioning
confidence: 99%